Aberrant Brain Function in Active-Stage Ulcerative Colitis Patients: A Resting-State Functional MRI Study - Fan, Weijie; Zhang, Si; Hu, Junhao; Liu, Bo; Wen, Li; Gong, Mingfu; Wang, Guangxian; Yang, Li; Chen, Yuyang; Chen, Heng; Guo, Hong; Zhang, Dong (Frontiers in Human Neuroscience, 2019)
Background: Patients with ulcerative colitis (UC) usually display cognitive impairments, such as memory loss, attention deficit and declining executive function, especially during active disease. However, the potential neurological mechanisms of these symptoms remain unclear. Method: Forty-one patients with mildly to moderately active UC, as well as forty-two matched healthy controls, were recruited for examination using psychological scales, cognitive function testing and resting-state functional magnetic resonance imaging (rs-fMRI). Seed points were identified via amplitude of low-frequency fluctuation (ALFF) analysis, and whole-brain functional connectivity (FC) was calculated based on the graph theoretical. Correlation analyses were performed among clinical indexes, neuropsychological assessments and neuroimaging data. Result: Compared with the healthy controls, UC patients exhibited lower ALFF values in the bilateral hippocampal/parahippocampal region and higher ALFF values in the left posterior cingulate cortex and left middle frontal gyrus. With HIPP/ParaHIPP as the seed point, activity in the FC in the bilateral middle frontal gyrus, anterior cingulate cortex, and left caudate nucleus increased; these brain regions are mainly related to working memory. Using the PCC.L as the seed point, activity in the FC in the middle cingulate cortex and the left angular gyrus increased; these brain regions are mainly related to the attention network and executive functions. Conclusion: These results indicated that the limbic lobe might be the core of the brain-gut axis and play an important role in cognitive impairments, suggesting potential mechanisms for cognitive impairment in UC patients during active disease.